2003
DOI: 10.1046/j.1525-139x.2003.16069.x
|View full text |Cite
|
Sign up to set email alerts
|

Interventional Nephrology and Dialysis: The Role of Sonography in the Planning of Arteriovenous Fistulas for Hemodialysis

Abstract: Patients presenting for initial access evaluation in contemporary practice are less likely to have arteries and veins suitable for native fistula (AVF) formation in the classic location. Physical examination of the upper extremity alone may be inadequate for selection of arteries and veins that will mature into a functioning AF. The purpose of this paper is to determine how duplex ultrasonography can be used as an effective modality for the preoperative evaluation of vessels before construction of arteriovenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 12 publications
0
58
0
2
Order By: Relevance
“…Alternatively, he/she may be seated in front of the operator with the forearm resting on a stand. Most examiners prefer the supine position because it simplifies the assessment of the vascular structures of the arm (subclavicular axillary region) and is more comfortable for the patient [13,14]. The examination should be carried out in a comfortably warm room, and the gel should also be warmed to avoid triggering vasoconstriction of the structures being examined [13,14].…”
Section: Technical Requirements and Examination Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, he/she may be seated in front of the operator with the forearm resting on a stand. Most examiners prefer the supine position because it simplifies the assessment of the vascular structures of the arm (subclavicular axillary region) and is more comfortable for the patient [13,14]. The examination should be carried out in a comfortably warm room, and the gel should also be warmed to avoid triggering vasoconstriction of the structures being examined [13,14].…”
Section: Technical Requirements and Examination Techniquementioning
confidence: 99%
“…Most examiners prefer the supine position because it simplifies the assessment of the vascular structures of the arm (subclavicular axillary region) and is more comfortable for the patient [13,14]. The examination should be carried out in a comfortably warm room, and the gel should also be warmed to avoid triggering vasoconstriction of the structures being examined [13,14]. Ideally, the arterial and venous districts should be evaluated consecutively, with transverse and/or longitudinal scans of the arteries (from the root of the arm towards the hand) and veins (from the periphery towards the thorax).…”
Section: Technical Requirements and Examination Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…The criteria on which a vessel is suitable for AVF creation by duplex ultrasound are not established. Many variables should be considered (89,92,93), and using minimal vessel diameter as a sole criterion should be avoided. Doing so may preclude the use of veins that would have been acceptable by clinical examination (24,94).…”
Section: Continue Fistula First With Review and Reevaluation Of The 1mentioning
confidence: 99%
“…These cells then could produce an array of mediators that hopefully would mimic the two main functions of endothelial cells (promote vascular dilation and inhibit neointimal hyperplasia). At a practical level, however, numerous clinical studies have been able to demonstrate a significant improvement in the maturation of AVF through an aggressive preoperative ultrasound evaluation of arterial and venous diameters (112)(113)(114). Malovrh et al (113), for example, demonstrated an immediate patency rate of 92% in patients with a preoperative internal diameter of Ͼ1.5 mm in the feeding artery as compared with a maturation rate of 45% in patients with an internal diameter of Ͻ1.5 mm.…”
Section: Promoting Native Avf Maturationmentioning
confidence: 99%